1996
DOI: 10.1109/10.486282
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic assessment of human and bovine trabecular bone: a comparison study

Abstract: A comparison study is reported on the ultrasonic assessment of human trabecular and bovine trabecular bone samples. Both ultrasonic velocity and ultrasonic attenuation were evaluated through a transmission insertion technique and correlated with bone mineral density as determined with single photon absorptiometry. For a 1-MHz ultrasonic transducer pair and the human cancellous bone samples the correlations were 0.91 and 0.89 between density and velocity and attenuation, respectively. For a 500-kHz ultrasonic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…In vitro experiments found high correlations between bone mechanical indices, such as the hardness of the bone and the indent depth of bone cores, with ultrasound measurements [5][6][7][8]. Measurement of bovine bone core samples demonstrated high correlation between QUS parameters and X-ray densitometry [9]. Subsequent cross-sectional studies in humans confirmed this relation between the broadband ultrasound attenuation (BUA), which is the attenuation of the sound wave as it passes through the bone, BMD as measured by DXA.…”
Section: Introductionmentioning
confidence: 84%
“…In vitro experiments found high correlations between bone mechanical indices, such as the hardness of the bone and the indent depth of bone cores, with ultrasound measurements [5][6][7][8]. Measurement of bovine bone core samples demonstrated high correlation between QUS parameters and X-ray densitometry [9]. Subsequent cross-sectional studies in humans confirmed this relation between the broadband ultrasound attenuation (BUA), which is the attenuation of the sound wave as it passes through the bone, BMD as measured by DXA.…”
Section: Introductionmentioning
confidence: 84%
“…There is growing interest in the use of quantitative ultrasound (QUS) in the diagnosis and management of osteoporosis. Initial assessment believed that QUS measured bone structure and bone quality [3][4][5], but there is mounting evidence to show that QUS primarily reflects bone density [6][7][8][9]. There is a high correlation found between in vivo QUS measurements and heel bone mineral density (BMD) measured by dualenergy X-ray absorptiometry (DXA) [9].…”
Section: Introductionmentioning
confidence: 98%
“…3 In contrast, several studies reported the nonlinear relationship between the attenuation and the bone mineral density (BMD) over a wide range of BMD. 13,14 For instance, Alves et al observed a positive correlation between the nBUA and the BMD in relatively low density human trabecular bone samples (0.057-0.142 gcm -3 ) and a negative correlation in higher density bovine samples (0.190-0.450 gcm -3 ). 13 Comparison of the present study with the works discussed in the preceding text is complicated by the fact that they used the BMD while the present study used the apparent bone density.…”
Section: Methodsmentioning
confidence: 96%
“…13,14 For instance, Alves et al observed a positive correlation between the nBUA and the BMD in relatively low density human trabecular bone samples (0.057-0.142 gcm -3 ) and a negative correlation in higher density bovine samples (0.190-0.450 gcm -3 ). 13 Comparison of the present study with the works discussed in the preceding text is complicated by the fact that they used the BMD while the present study used the apparent bone density. Figure 3 shows the average backscatter coefficient as a function of the frequency for the 25 bone samples.…”
Section: Methodsmentioning
confidence: 96%